Paraaortic Thymoma with Pericardial Effusion Diagnosed by Transthoracic Echocardiography in a Woman with Myasthenia Gravis. Issue 5 (11th January 2013) - Santoro, Francesco; Russo, Anna Rita; Lupo, Pierluigi; De, Luisa; Gianfrancesco, Domenico; Biase, Matteo Di; Brunetti, Natale Daniele
Mini‐Abstract We report the case of a 64‐year‐old woman with myasthenia gravis, dyspnea, and pericardial effusion. Echocardiography showed a paraaortic mass, confirmed at computed tomography scan, which was later diagnosed as a thymoma after surgical excision.